How Leadership Perception and Interpersonal Communication Shape Academic Wellbeing: Evidence from Islamic Higher Education - Novita, Wirda; Wijaya, Candra; Mukti, Abd. (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the causal relationships between Leadership perception, interpersonal communication, work climate, and lecturers' job satisfaction. Rapid changes in Islamic higher education governance require a deeper understanding of how organisational dynamics shape academic Wellbeing and institutional performance. Using a quantitative, path-analytic approach, this research investigates both direct and indirect effects among the four variables. Data were collected from 100 lecturers selected through the Krejcie and Morgan sampling Table, using a structured Likert-scale questionnaire that had undergone validity and reliability testing. The findings indicate that Leadership perception and interpersonal communication significantly influence work climate, with interpersonal communication emerging as the strongest predictor. Leadership perception, interpersonal communication, and work climate each have significant direct effects on job satisfaction, with work climate making the most important contribution. The analysis also confirms that work climate partially mediates the relationship between Leadership perception and interpersonal communication toward job satisfaction. The structural model demonstrates strong explanatory power, accounting for 85 per cent of the variance in work climate and 87 per cent of the variance in job satisfaction. These results imply the essential role of supportive Leadership practices, open communication, and a cohesive work environment in enhancing lecturer satisfaction.